“Auntie Lucy” 男扮女装的操弄策略 = Manipulative strategy of "Auntie Lucy" 's cross-dressing - 郭思慧 Quek, Ser Hwee (2013)
“Auntie Lucy”原是新加坡新传媒私人有限公司（Media Corporation of Singapore Pte Ltd）华文电视频道的处境剧《女王本色》（2009年）中的一个主角。“Auntie Lucy”以男扮女装的表演方式，讽刺新加坡社会中的文化陋习，而电视人物自2009年在短时间内窜红，广受新加坡华文观众、广告商与片商的欢迎，成为新加坡家喻户晓的喜剧角色。人物塑造的成功，连带提升扮演“Auntie Lucy”的男演员周崇庆的知名度，为他带来无数的奖项，更让他二十三年的演艺事业中，臻至巅峰。不过，《女王本色》一剧，透过综艺喜剧节目惯用的夸张搞笑手法，以及“Aunty Lucy”通俗夸张的男扮女装演绎方式，带出新加坡社会对于性别定型的僵化思考。除丑化女性、深化性别差异外，《女王本色》建构另一层性别刻板定型的议题，更通过节目为场域、嘲谑与调侃“Auntie Lucy”为工具，试图达到社会改革的目标。这些别有深意的议题，都值得我们进一步去探讨。因此，“Aunty Lucy”作为一个文化现象，值得置于流行文化及性别研究的框架里来分析。本文拟以“Auntie Lucy”作为文本，深入讨论大众通俗文化背后，隐藏的操弄策略与社会蕴涵。通过解构“Auntie Lucy”从仪表打扮、行为举止到谈吐修养的整体形象，能检视一般民众对“Auntie Lucy”这样的大众通俗文化所忽视的更深层的问题，意即大众通俗文化延伸出的文化批判、性别定型与国家意识形态的议题。"Auntie Lucy" was originally a supporting role in MediaCorp's Mandarin situational comedy Paris and Milan. The television cross-dresser rose to fame in 2009 and became a well-known cultural symbol in Singapore, widely popular among the Chinese-speaking audience, advertisers and film production company. The television character's success catapulted male actor Dennis Chew to success and his rising popularity as "Auntie Lucy" helped him won numerous award recognitions for the first time in twenty-three years of his career as an artiste. The following thesis seeks to use "Auntie Lucy" as a text and combine academic discourse to examine deeper topics such as the manipulative strategy and social implication behind mass popular culture. As "Auntie Lucy" has yet to surface in any academic research, the character's role as a cultural symbol deserves to be placed in an academic discussion. Through the deconstruction of "Auntie Lucy"'s overall image with reference to her dressing, behavior and speech, this paper yields insight into a deeper discussion of issues often overlooked by the general public, namely in the areas of cultural criticism, gender stereotype and state ideology.